2017
DOI: 10.1186/s12933-017-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 diabetes mellitus on in-hospital-mortality after major cardiovascular events in Spain (2002–2014)

Abstract: BackgroundDiabetes mellitus has long been associated with cardiovascular events. Nevertheless, the higher burden of traditional cardiovascular risk factors reported in high-income countries is offset by a more widespread use of preventive measures and revascularization or other invasive procedures. The aim of this investigation is to describe trends in number of cases and outcomes, in-hospital mortality (IHM) and length of hospital stay (LHS), of hospital admissions for major cardiovascular events between type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
8
40
2
1
Order By: Relevance
“…Whether in the American, European, or other countries of the world, ACS patients with diabetes is common (usually greater than one-third of patients) and associated with a higher risk of death and other adverse events [ 2 5 , 38 ]. Although studies have reported that the cardiovascular outcomes of diabetes have been improved in recent years, number of people with diabetes still rises, the absolute burden of CVD will still be high [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether in the American, European, or other countries of the world, ACS patients with diabetes is common (usually greater than one-third of patients) and associated with a higher risk of death and other adverse events [ 2 5 , 38 ]. Although studies have reported that the cardiovascular outcomes of diabetes have been improved in recent years, number of people with diabetes still rises, the absolute burden of CVD will still be high [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global burden of diabetes mellitus (DM) rises with ageing, and is accompanied by a high mortality among affected individuals [ 8 ]. In Taiwan, a nationwide survey found that the overall incidence of DM rose from 0.76 to 0.93% within 10 years, equivalent to a 25% increase, and there were 1.22 million Taiwanese affected by DM in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes is occurring at an epidemic rate globally . It is one of the leading causes of cardiovascular events and death, resulting in a growing economic burden on the national health care system and an ongoing negative impact on health‐related quality of life . Accumulating evidence shows that physical activity, which characterizes the behavior of any bodily movement produced by skeletal muscle contraction , is a modifiable protective factor against the onset of type 2 diabetes .…”
Section: Introductionmentioning
confidence: 99%